The cardiovascular effects of SGLT2 inhibitors, RAS inhibitors, and ARN inhibitors in heart failure - Peng‐juan Ji; Zhuo‐ya Zhang; Qi Yan; Hui‐li Cao; Ya‐jing Zhao; Bin Yang; Jin Li (ESC Heart Failure, 2023)
Abstract Aims No studies have comprehensively compared the efficacy of sodium‐glucose cotransporter‐2 (SGLT2) inhibitors, renin–angiotensin system (RAS) inhibitors, and angiotensin receptor neprilysin (ARN) inhibitors based on different type of heart failure, including heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF). The aim of this network meta‐analysis was to evaluate the relative efficacy of SGLT2 inhibitor (SGLT2i), RAS inhibitor (RASi) and ARN inhibitor (ARNI) in different types of heart failure. Methods A systemic literature search was performed from inception to 19 November 2022 for randomized control trials assessing the risk of cardiovascular (CV) death or hospitalization for heart failure (HHF) of these drugs in HF. A network meta‐analysis was performed. Risk ratio (RR) with 95% confidence intervals (CI) were synthesized. Results Seventeen studies were selected with a total of 61 489 patients. In patients with HFrEF, ARNI led to a reduced risk of a composite outcome of CV death or HHF when compared with placebo (RR = 0.83, 95% CI 0.77–0.89). Similar trends were observed when focusing on the outcome of CV death or HHF alone. In patients with HFpEF, SGLT2i showed the beneficial effects on the CV death or HHF events when compared with placebo and RASi (RR = 0.82, 95% CI 0.74–0.92; RR = 1.16, 95% CI 1.02–1.31). For CV death, all these three drugs could not show beneficial effects in HFpEF. For the incidence of HHF in HFpEF, both SGLT2i and ARNI demonstrated the beneficial effects but SGLT2i was superior to ARNI. There were no differences in the events of discontinuation under these drugs when compared with placebo or each other in either HFrEF or HFpEF patients. SGLT2i showed the least renal injury among these interventions in HFrEF and there were no differences in the incidence of renal injury of these interventions in HFpEF. Conclusions Among these drugs, ARNI showed the greatest ability to lower the incidence of CV death or HHF and SGLT2i exerted the least renal injury in patients with HFrEF. In patients with HFpEF, SGLT2i was associated with a reduction in the risk of CV death or HHF. There were no differences in the incidence of renal injury of these interventions in HFpEF. The intolerance of these drugs were comparable in both HFrEF and HFpEF.